Shifts in regional employment: an application of the Haynes-Dinc model for Brazil - José Paulo Chahad; Antonio Evaldo Comune; Eduardo Haddad (European Regional Science Association (ERSA), 2002)
Brazil has undergone deep structural changes in the 1990s with strong implications for the labor markets. The overall decrease in employment levels in Brazil, since the early 1990s, is evident from official statistics. However, the sectoral and regional mapping of this shift has not been properly studied yet. In this paper, we use the Haynes-Dinc shift-share model to measure the impact of output change, productivity gain and other non-labor factors on employment change in the period 1992-1996.
Keywords: 330